Mixed spices increase serum adiponectin protein (Adipokine) and insulin in STZ induced hypergylcemia rats - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim (Universite Laval, 2010)
Spices are used in food around the world with a view to enhance the flavor/aroma of dietary preparations. Apart from this aspect spices are also used in herbal medicines practice/treatment. Therefore, spices have been studied extensively in relation to their effectiveness in the prevention/control of certain disease conditions. Numerous studies have shown that spices consumed as part of food provide best control over diabetes (hyperglycemia). Therefore, this project was designed to study the effect of mixed spices namely cinnamon (Cinnamomum zeylanicum), cloves (Syzygium aromaticum or Eugenia caryophyllata), turmeric (Curcuma longa), and bay leaves also known as curry leaf (Murraya koenigii) on serum glucose, insulin and adiponectin protein concentration in rats induced hyperglycemia with streptozotocin (STZ). Sprague Dawley rats aged three months were injected with 40mg/kg body weight with STZ in the abdomen in order to induce hyperglycemia. The rats were acclimatized with diets prior allocation to the doses of mixed spices. After having developed hyperglycemia, the rats were divided into four groups i.e. 0 (control), one, two and three gram per day. The aforementioned spices were ground and mixed in equal ratios and added to stock diets 0, 1, 2 and 3 gram of the mixed spices in the feed to be fed to rats daily. The total duration of the feeding was 40 days and followed by 20 days after effect of the spices. The rats blood was collected on the day 0, 21, 31, 41 from the tail and on the 61st day from heart puncture of the rats. The blood samples were immediately processed for serum separation after each collection and stored for later analysis at -70 C. The serum was analyzed for adiponectin protein, insulin and glucose. The statistical analysis of the results indicated that serum adiponectin protein and insulin concentration were significantly (P<0.05) higher whereas serum triglycerides concentration was significantly (P<0.05) lower in three gram fed spices compared to control 1 and 2 gram spices fed groups. This study indicates that spices provide control over hyperglycemia through increased adiponectin and insulin in circulating blood.